NATIONAL LAND AGENCY POLICY TOWARDS LAND OWNERSHIP OF MODERN BURIAL SITES FOR COMMERCIAL VALUE-BASED SOCIAL JUSTICE (STUDY OF THE MODERN SAN DIEGO HILLS CEMETERY IN KARAWANG DISTRICT, WEST JAVA) - Junaedi Junaedi (Journal Indonesia Law and Policy Review, 2019)
This research aims to examine the mechanism for granting permits for management of Modern Cemetery Place Land San Diego Hills by Karawang regency government, West Java. This research is descriptive qualitative, the results of the study show that there are irregularities found in the management of modern San Diego Hills cemeteries, including the area of ​​cemeteries that are not by applicable laws and regulations, management Funerals are intended for private commercial interests, and deviations of tomb functions that are supposed to be in the public interest are transformed into individual interests, and based on this, government policy is needed to be firm and conscientious in granting operational licenses al for the private sector, as well as supervision over the implementation of operational licenses for modern burial sites that have been issued so that the function and purpose of the permit issuance are carried out accordingly.